Stakeholders’ Perspectives on Developing a Zero-Waste Integration System for Horticulture and Beef Cattle in Barru Regency: A Qualitatif Analysis - Astati, Astati; Hifizah, Amriana; Qurniawan, Anas (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
An integrated farming system that combines the horticulture and beef cattle subsectors based on the zero-waste principle is one of the innovative solutions to reduce negative environmental impacts while increasing production efficiency. Barru Regency, with its potential in horticulture and livestock, is a strategic area for the implementation of this system. However, the success of its implementation highly depends on the active involvement of various stakeholders. This study aims to examine stakeholders' perspectives on the development of a zero waste integration system of horticultural crops and cattle in Barru Regency. A qualitative approach was used to explore the perceptions, interests, roles, and challenges faced by stakeholders in the implementation of this system. Data were collected through in depth interviews, including Focus Group Discussions (FGD), participatory observations, and document studies. The informant sources identified in this study consist of 15 cattle farmers, 10 horticulture farmers, 2 field extension officers, 1 government official, and 1 academics. The data were analyzed using thematic analysis methods. The research findings show that 80% of farmers perceive waste reuse as economically beneficial, and 40% lack access to composting and biogas technology. Based on these findings, synergy among actors, regulatory strengthening, and inclusive policy support are needed to realize a sustainable zero-waste farming system.